Implementasi Kebijakan Pembiayaan Pendidikan Diniyah Takmiliyah di Kabupaten Bogor Berdasarkan Peraturan Daerah Nomor 2 Tahun 2019 - Ahmad Rafe'i; M. Maulana Nur Kholis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the implementation of financing policies for Diniyah Takmiliyah education in Bogor Regency based on Regional Regulation Number 2 of 2019. Diniyah Takmiliyah education plays a strategic role in strengthening religious understanding among Muslim communities in Indonesia, particularly in Bogor Regency. This research aims to analyze financing mechanisms, policy implementation, challenges faced, and the impact of policies on improving the quality of Diniyah Takmiliyah education. The research method employed is descriptive qualitative with data collection techniques through in-depth interviews, field observations, and documentation studies of relevant regulations. The research findings indicate that financing policy implementation involves the Education Office and Diniyah Takmiliyah educational institutions as primary implementers, with funding sources from regional budgets (APBD), sponsors, and community donations. Although this policy has had a positive impact on increasing access and quality of Diniyah education, there are several significant obstacles such as limited human resources and budgets, complex bureaucracy, regulations that are not fully integrated, and ineffective inter-agency coordination. Public awareness about the importance of Diniyah education also poses a particular challenge affecting participation rates. This study recommends the need for bureaucratic simplification, strengthened coordination among stakeholders, increased budget allocation, and intensive socialization to the community to optimize the implementation of Diniyah Takmiliyah education financing policies in Bogor Regency.